Documentation and record: Reflections on Le Corbusier´s journey to South America - Mata Quesada, Carlos (2023)
This article seeks to approach the background and motivations that ignited Le Corbusier's first trip to South America. It is based on two main derivatives: On one hand, it is directed to approach and understand certain elements of the journey undertaken in 1929 by the French-Swiss architect. On the other hand, it is aimed at building a private file to reflect on the ideas of the documentation, registration, travel and chronicle as practices and operations which is reflected in the logistics of the processes of designing, learning, and understanding architecture. In addition, the article´s purpose is to see these processes as part of the modern tradition with all the inherent elements of the discipline's own processes, something that Le Corbusier himself did not escape from. In this sense, it is necessary to reflect on these conditions in order to understand them within what has to be called the project of modernity, and how the ideas of travel and its recording begin to be fundamental elements as part of its expansive condition, consumption and the proto globalization of the modern world. In this sense, the condition of traveling, the construction of the record and the chronicle, have a sine qua non condition to it which is seen from the middle of the 18th century until a great portion of the 20th century.